Effects of alpha-mangostin encapsulated in nanostructured lipid carriers in mice with cerebral ischemia reperfusion injury - Romgase Sakamula,; Wachiryah Thong-asa,; Teerapong Yata, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Cerebral ischemia reperfusion injury (CIRI) is a phenomenon in which the cerebral blood supply is restored after a period of ischemia, resulting in irreversible damage to brain tissue. Oxidative stress plays a crucial role in the development of CIRI, therefore, targeting oxidative stress might be an effective strategy for CIRI prevention and treatment. Many therapeutic substances possess antioxidant and protective properties against neurodegenerative disorders but lack of in vivo application due to their solubility, and bioavailability. We investigated the effects of alpha-mangostin (αM) encapsulated in nanostructured lipid carriers (αM-NLC) on CIRI in mice. Forty male ICR mice were randomly divided into four groups: Sham, ischemia reperfusion (IR), ischemia reperfusion with 25 mg/kg of αM (IR+αM), and ischemia reperfusion with 25 mg/kg of αM-NLC (IR+αM-NLC). After 6 days of oral administrations, IR was delivered using 30 min of bilateral common carotid artery occlusion, followed by 45 min of reperfusion. Cerebral infarction volume, hippocampal neuronal and corpus callosum (CC) white matter damage, malondialdehyde (MDA) level, and catalase (CAT) activity were evaluated. Our results indicated that αM and αM-NLC prevent lipid peroxidation as well as hippocampal CA1, CA3, and CC damage (p<0.05). Only αM-NLC prevented cerebral infarction and enhanced CAT activity (p<0.05). We therefore conclude that αM and αM-NLC have neuroprotective effects against CIRI, and NLC increases therapeutic efficacy of αM against CIRI.